Rainfall Variability Index (RVI) Analysis of Dry Spells In Malaysia - Chung, Jing Way (2021)
The lower number of rainfall events causing the environment to become drier over the years is a crucial phenomenon attracting the concern of all around the world. The impacts of rainfall event deficiencies will lead to the issues of availability of water resources, both for the agricultural sector and the human health development. Therefore, the studies on the rainfall variability in term of the dry spells (DS) and the drought characteristics of the regions are necessary for a better understanding for the DS and their associated spatial and temporal variations. In this study, the study period is from 1988 to 2017, and the intricacies of the DS and extreme DS occurrences, spatial distribution for drought characteristics over Malaysia were analysed. The study was confined to the 30-year period of monthly and annual rainfall data that was graciously provided by the Malaysian Meteorological Department and the Drainage and Irrigation Department. All of the raw data were then analysed using the Rainfall Variability Index (RVI) with two different timeframes, that being the 30-year long-term period and subsequently over six 5-year sub-periods consecutive sections of the 30-year long period. The findings showed that the Northern Region and Central Region located in Peninsular Malaysia, and the regions that lie between Sabah and Sarawak had more DS occurrences due to the higher number DS exhibited over the study period. The next part of the study was the spatial analysis for drought frequency (DF) and mean drought duration (MDD) over the 13 regions throughout Malaysia. It showed that the DF was significant for both the annual and monthly RVI, and for the MDD significant for the monthly RVI over the 30-year period. For the six 5-year sub-periods, the spatial differences varied for both DF and MDD, based on annual RVI.